2022
DOI: 10.1111/jdi.13775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucagon‐like peptide‐1 receptor agonists on fat distribution in patients with type 2 diabetes: A systematic review and meta‐analysis

Abstract: Aims/Introduction Glucagon‐like peptide‐1 receptor agonists (GLP‐1Ras) are widely used to treat type 2 diabetes. They not only reduce glucose, but also have a positive effect on weight loss. However, few studies have reported the effect of GLP‐1Ras on fat distribution. Materials and Methods PubMed, Cochrane, Embase and ClinicalTrials.gov were searched for randomized controlled trials on GLP‐1Ras and type 2 diabetes, published from inception to June 2021. Our main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Our safety findings on liraglutide are consistent with those of a previous meta‐analysis 10 . None of the included studies reported adverse hypoglycaemic events or hepatic or renal insufficiency following therapy with liraglutide.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our safety findings on liraglutide are consistent with those of a previous meta‐analysis 10 . None of the included studies reported adverse hypoglycaemic events or hepatic or renal insufficiency following therapy with liraglutide.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with those of a previous meta-analysis that included patients with T2DM. 10 However, we provide an explanation for the cardiometabolic benefits of liraglutide in obese and overweight patients without T2DM.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…GLP‐1 RAs lower glucose levels by direct and indirect actions on several organs, including the central nervous system, heart, arteries, kidneys, liver and pancreas 13 . A recent systematic review and meta‐analysis 14 also showed that GLP‐1RAs significantly reduce both visceral adipose tissue and subcutaneous adipose tissue, and the decrease of visceral adipose tissue was greater than that of subcutaneous adipose tissue when compared with the control group.…”
Section: Figurementioning
confidence: 99%